Myofunctional Treatment of Anterior Openbite With Preorthodontic Trainer: Report of a Case - Defne Keçik; Ayhan Enacar (Galenos Yayinevi, 2009)
This case report describes the treatment of a 11,2 year-old girl presenting an anterior openbite due to abnormal swallowing habits, tongue thrust and mouth breathing, treated with Preorthodontic TrainerTM (T4KTM Myofunctional Research Co. Helensvale, Australia) appliance. The patient had a skeletal Class I relationship with a 3mm of openbite and 2mm of overjet as well as a normal profile. The molar and canine relationships were Class I. The patient used the preorthodontic trainer for 8 months to eliminate the mouth breathing and stimulate nose breathing, eliminate the tongue thrust and close the bite. The patient was instructed to use the second phase appliance of preorthodontic trainer for retention during the 1-year period. At the end of the treatment the openbite was eliminated as well as the tongue thrust habit. The Class I relationship was maintained and a stable dentofacial relationship was established. At the follow up period the overbite increased and the treatment results were maintained.